USULAN PERBAIKAN PROSES PRODUKSI DI PERCETAKAN TRIBUN MANADO MENGGUNAKAN METODE DMAIC SIX SIGMA - Paat, Geraldo; Rottie, Ronaldo; Raton, Yulius C. (Fakultas Teknik, Universitas Katolik De La Salle Manado, 2018)
A Proposal to improve production in Tribun printing Manado using the DMAIC Six Sigma method. In the background is the rapid development of technology that requires a printing company to use machines instead of humans to speed up theproduction process to supply the market's demand. But new problems encountered, the faster the production process the more the product will be defective. The same problem is also faced by Tribun Manado printing. From the data obtained from February to April, the average newspaper produced each month reached 1,088,345 copies with average product defects of 32,651 copies. Based on these data a DMAIC Six Sigma method is used (Define, Measure, Analysis, Improve, Control) to analyze and look for factors that cause waste or defect during the production process. The stages of DMAIC begin with the Define stage. At the define stage a project charter is created, containing the description of the defective product problem. Making SIPOC diagram to know the interaction involved in the production process starts from the ordering of raw materials then news writing, editorial stage, layout, production process until dissemination then determination CTQ where CTQ found in Tribun Manado printing is 3 CTQ. At the measure stage the NP chart is created. From a presentation made from NP chart, the resulting product defect reaches 3%, Cp 0.7, DPMO 30000 average with a low 3.4 sigma valueindicates printing needs improvement. At the stage of analysis, a diagram Ishikawa is made to describe the root cause of each CTQ, and it is found: shaded writing, blurred image color and writing and a color mismatch. At the step of improve an FMEA table is made, containing an improvement proposal based on problems found using diagram Ishikawa on analysis stage, then in the Control stage an action plan is made to check whether the proposals made have yet been applied or not.